Human Dialyzable Leukocyte Extract Enhances Albendazole Efficacy and Promotes Th1/Th2-Biased Lymphocyte and Antibody Responses in Peritoneal Cavity of Murine Model of Mesocestoides vogae Infection - Hrčková, Gabriela; Mudroňová, Dagmar; Reiterová, Katarína; Cavallero, Serena; Bellini, Ilaria (International Journal of Molecular Sciences, 2025)
Human leukocyte extract (HLE), a non-immunogenic dialyzable leukocyte preparation (<10 kDa), may serve as a safe adjuvant in immunotherapy. We investigated the effects of albendazole (ABZ), HLE, and their combination in Mesocestoides vogae infected mice, focusing on lymphoid cells in the peritoneal cavity, the site of larval proliferation and parasite-induced immunosuppression. Peritoneal lymphoid cells were analysed by flow cytometry and qPCR. Cells proliferative responses to ConA, LPS, and parasite excretory/secretory (E/S) antigens, cytokine production (ELISA), IgM and IgG isotypes in exudates and parasite antigen recognition (Western blot) were assessed. Efficacy was measured by larval burden and 14-3-3 gene expression in larvae. HLE combined with ABZ enhanced larval clearance and suppressed 14-3-3 gene expression in larvae. HLE and combination therapy increased CD3+ T cell frequencies, especially CD3+high, reduced regulatory CD3+/IL-10 Tregs and expression of Foxp3+. All treatments diminished CD19+/IL-10+ Bregs, correlating with lower CD9 and Atf3 mRNA levels compared to infected mice. Transcription factors T-bet expression was strongly upregulated, while GATA3 was moderately elevated. IFN-γ production and T/B cell proliferation were restored after HLE and combination therapy, partially, even in the presence of E/S antigens. IgM and total IgG levels against parasite antigens declined, while Th1-associated IgG2a increased in ABZ+HLE and HLE-treated groups. Albendazole failed to reverse the immunosuppressive Treg-type immunity but was more effective in reducing Breg populations and their functions. HLE enhanced ABZ efficacy by restoring Th1 responsiveness, reducing Treg/Breg activity, and modulating antibody profiles. It represents a promising immunomodulatory adjuvant in the treatment of the infections associated with Th2/Treg-driven immunosuppression.